(3CQLhRI aj GdQeis - (3WjHZG GdHcGTi GdjhfGfis ((3CMeO Hf eMeO Hf GdLgfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi YdefG YdekG Hg Hjf GdhQi TQafG YdefG GdQei GdSOjO GdfGci hNUfG bOQG YdjG RGci s
(3BNQgG (B:s
(3JeJ GdCQLhRI GdeHGQcI aEfgG HTQMgG aGJcI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3QVGQGeHhQ (B(3535) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs